Experimental tests of survey responses to expenditure questions - David Comerford; Liam Delaney; Colm Harmon (Institute for the Study of Labor (IZA), 2009)
This paper tests for a number of survey effects in the elicitation of expenditure items. In particular we examine the extent to which individuals use features of the expenditure question to construct their answers. We test whether respondents interpret question wording as researchers intend and examine the extent to which prompts, clarifications and seemingly arbitrary features of survey design influence expenditure reports. We find that over one quarter of respondents have difficulty distinguishing between you and your household when making expenditure reports; that respondents report higher pro-rata expenditure when asked to give responses on a weekly as opposed to monthly or annual time scale; that respondents give higher estimates when using a scale with a higher mid-point; and that respondents report higher aggregated expenditure when categories are presented in a disaggregated form. In summary, expenditure reports are constructed using convenient rules of thumb and available information, which will depend on the characteristics of the respondent, the expenditure domain and features of the survey question. It is crucial to further account for these features in ongoing surveys.
Keywords: D03; D12; C81; C93; 330; Expenditure surveys; survey design; data experiments; Verbraucherausgaben; Befragung; Test